호스피스병동 말기 암 환자 및 내과의사의 사전의료지시(서)에 대한 인식 - 손덕승; 전연주; 이정화; 길상현; 심병용; 이옥경; 정인순; 김훈교; Sun, Der-Sheng; Chun, Yeon-Joo; Lee, Jeong-Hwa; Gil, Sang-Hyun; et al. (Han'guk Hosŭpʻisŭ Wanhwa Uiryo Hakhoe chi = The Korean journal of hospice and palliative care, 2009)
Purpose: We undertook this study to find out the recognitions of terminal cancer patients and doctors about advance directives (ADs), of how they would do in non-response medical conditions and whether ADs could be one of medical options for their dying with dignity. Methods: One hundred thirty four cancer patients in the Hospice Unit, St. Vincent's Hospital, and 97 medical doctors in the Department of Internal Medicine, Catholic Medical Center, were asked about ADs, including Do-Not-Resuscitate (DNR), medical power of attorney, living will and medical options. Results: One hundred thirty patients (97%) and 38 doctors (39.2%) were unfamiliar with ADs, however, 128 patients (95.5%), 95 doctors (97.9%) agreed with it. Seventy nine patients (59.0%) and 96 doctors (99.0%) wanted DNR rather then intensive treatments if they were in non-response medical conditions. Eighty four patients (62.7%) and 75 doctors (77.3%) were agreeable to medical power of attorney. One hundred Thirty four patients (100.0%) and 94 doctors (96.9%) did not want medical options to be in terminal conditions, and hoped to die in peace. Conclusion: Most of patients did not know about ADs and how to make it. However, they showed positive attitudes about it. If we advertise it properly, it is highly likely that a large number of cancer patients would make their living wills easily by ADs. Nevertheless, many legal and ethical problems have to be solved. Doctors should engage their patients in an ongoing communication about the end-of-life. Therefore, let the patients have opportunities to plan their own deaths. 목적: 말기 암 환자와 의사를 대상으로 추후 의료적 치료 결정을 내리지 못하는 경우를 대비하여 심폐소생술 거부, 의료적 권한 법정 대리인, 생존시 유언장을 포함한 사전의료지시(서)에 대한 인식을 알아보고자 하였다. 방법: 2007년 5월부터 11월까지 가톨릭대학교 성빈센트병원 호스피스 병동으로 내원한 말기 암 환자와 가톨릭중앙의료원 2, 3, 4년차 내과 전공의(의사)를 대상으로 사전의료지시에 대해 구조화된 설문지를 이용한 조사를 실시하였으며, 환자 134명, 의사 97명으로부터 답변을 받았다. 결과: 환자 128명(95.5%), 의사 95명(97.9%)은 사전의료지시를 찬성하였으며, 환자 79명(59.0%), 의사 96명 (99.0%)은 추후 치료에 반응하지 않는 말기 상태일 경우 무의미한 생명연장을 위한 심폐소생술을 원치 않았고, 환자 85명(63.4%), 의사 75명(77.3%)은 본인이 의사결정을 할 수 없는 상황일 때를 대비한 의료적 권한 법정 대리인 지정에 찬성 하였다. 예로 제시된 유언장 내용에서 설문에 응한 환자 134명(100%), 의사 94명(96.9%)은 말기 상황일 경우, 가능한 편안하게 사망할 수 있도록 자신에게 시행되는 모든 치료를 중단, 보류하기를 원하였다. 결론: 본 연구에서 말기 암 환자와 의사는 인생의 마지막을 결정짓는 도구로 사전의료지시(서)에 대해 긍정적이고 적극적인 태도를 보였다. 하지만, 아직 법적, 사회적 합의가 없어 하나의 체계로 정립되지 못하고 있다. 여러 쟁점이 해결되어 힘들게 투병하고 있는 말기암 환자에게 사전의료지시(서)가 보편적이고 합법적인 의료 체계로 확립된다면 그들 인생의 마지막을 존엄하게 맺을 수 있는 선택이 될 것으로 생각한다.